Heavy Metals in Baby Foods and Cereal Products (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Lead and cadmium are toxic elements; when ingested or inhaled, they can lead to several diseases, a list of which is shown below. The diseases affect children, especially infants under the age of five. This work analyzes 63 baby foods and cereal products for lead and cadmium, and the analysis is done with an atomic absorption spectrophotometer (AAS) with a Shimadzu double-beam atomic absorption analyzer, AA-6300. Lead and cadmium were established to vary between 0.32- 10.64μ g/kg and 0.3-10.37 μg /kg, respectively. Altogether, 49.21% of the samples have lead above the LOD, while the rest have it below this value. In the samples analyzed for cadmium, more than 85 percent of the samples had detectable levels. The results of lead and cadmium in the milk powder products were relatively low, with the said metals detected at levels below 10μg/kg in all the samples, being between 0.85- 7.26 μg / kg for lead and between 0.1 – 4.75 μg /kg for cadmium. The young infants were most exposed to these heavy metals through the consumption of cereal-based products. Still, in any case, the calculated concentrations were lower than the permitted regulatory limits prescribed by Commission Regulation (EC) No 1881/2006, which limits the metals in food to 20μg/kg for lead in infant formula and 100 μg/kg for cadmium in cereals (EC 2006). As much as the levels established in this study were within the legal limits, the high prevalence of lead and cadmium added to baby foods poses future health risks to vulnerable groups, requires more raw material and processing control, and better regulation of admixture safety standards.